The determinants of the intention to use cryptocurrency for financial transactions: The mediating role of perceived risk in the UTAUT framework - Yamout, Racha; Saad, Rachel; Abass, Alaa Eldin; ElMoussaoui, Ali (Edelweiss Applied Science and Technology, 2025)
Cryptocurrency is experiencing exponential growth, attaining a total market capitalization of 3.86 trillion dollars in 2025. The research focuses on examining the factors affecting the intention to use cryptocurrency for financial transactions in Lebanon. In a high-risk economy where trust in banks has been devastated since the 2019 banking crisis, it is crucial to analyze the factors that influence the willingness to adopt cryptocurrencies. This study employs the partial least squares method, the SEM model, and the bootstrapping technique on a sample of 400 Lebanese entrepreneurs and business owners who either use cryptocurrencies or intend to include them in their firm’s financial activities. By examining the relationship between independent variables such as social influence, financial literacy, and perceived risk, and their impact on the intention to use cryptocurrency for financial transactions, the research contributes to both academic understanding and practical implications regarding the adoption of this innovative technology in emerging countries. Empirical results indicate that social influence and financial literacy significantly affect the intention to adopt cryptocurrencies. However, perceived risk did not diminish the willingness to adopt cryptocurrencies. This study addresses a gap in the literature by highlighting the factors influencing the intention to use cryptocurrencies for financial transactions in Lebanon.